CircRNA-1806 Decreases T Cell Apoptosis and Prolongs Survival of Mice After Cryptococcal Infection by Sponging miRNA-126 - Zhang, Lei; Zhang, Keming; Fang, Wenjie; Li, Hang; Li, Yingfang; Jiang, Weiwei; Hu, Dongying; Coelho, Carolina; Liu, Xiaogang; Cai, Liangqi; Liao, Wanqing; Pan, Weihua (Frontiers in Microbiology, 2020)
CircRNAs are a recently well-known regulator that mediates a variety of biological processes. Cryptococcus neoformans is an environmental fungal pathogen that can cause fatal cryptococcal meningitis in immunocompromised individuals. However, the involvement of circRNA in cryptococcal infection remains unclear. In this study, high‐throughput microarray was performed to identify the circRNA expression profile in cryptococcal meningitis patients. Circ_0001806 was significantly decreased in cryptococcal meningitis individuals. Then the effects of circ_0001806 and its interaction with miRNAs were explored in vivo and in vitro. The knock-down of circ_0001806 led to higher fungal infection and shorter survival in an experimental murine cryptococcosis model. Transcriptome analysis showed that decreased circ_0001806 regulated pathways related to the host antimicrobe response in T cells. Furthermore, in vitro experiments showed that circ_0001806 positively modulates ADM level, decreasing cell apoptosis and G1S arrest in T cells. At last, we found circ_0001806 exerted its effects by sponging miRNA-126 in T cells. Taken together, our results reveal the role of circRNA-1806/ miRNA-126 in the regulation of cell cycle and apoptosis in cryptococcal infection and can provide a new window for the pathogenesis of cryptococcal infection.